Dynamics of Micro and Small Enterprises Performance in Nigeria: The Effect of Internal Motivation - Imam , Maryam Ibrahim; Bukar, Alhaji Zubairu; Kyari, Zanna Sunoma; Ibrahim, Lawan Mustapha (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
To increase the credibility of a results in quantitative investigation, the instrument used in data collection is the most crucial part of the study. However, to get a good result of validity and reliability, researchers need to design and conduct a proper pilot test. The aim of pilot test is to evaluate the level of validity and reliability on the research instrument. To achieve this, a sample of the questionnaire was distributed to experts in the field of management, specifically academicians to make useful comments and inputs on the suitability of the items adapted to measure the constructs. Additionally, the survey method was used to gather response through 50 usable questionnaires administered to micro and small business owner-managers in Kano, the largest commercial center in northern Nigeria, stratified random sampling was applied for data collection. The data was analyzed using SPSS V20. Findings reveal evidence of reliability of the instrument, indicating that all the items are found to be reliable as the Cronbach’s alpha values ranges from 0.62 to 0.87.